Utilizing Microbiome Approaches for Antibiotic Resistance Analysis; an Ocular Case Evaluation - Kavianfar, Azadeh; Taherkhani, Hamidreza; Ghorbani, Fatemeh (Journal of Ophthalmic and Optometric Sciences, 2021)
Background: Metaorganism or microbial communities of eukaryotic organisms provide an inclusive set of functions related to immunity, host metabolism, and stress tolerance. Ocular microbiota refers to pathogenic and commensal microorganisms in or on the eye. On the one hand, antibiotic treatment can give rise to pathogen overgrowth due to an imbalance of microbiota and cause various ophthalmic diseases. On the other, antibiotic therapy is considered the leading cause of antibiotic resistance. The present study aimed to describe the bacterial community changes following antibiotic treatment in the ocular surface microbiome. Material and Methods: In this scenario, we evaluated the composition of thirteen canine ocular microbiomes during treatment with a typical mixture of antibiotics, neomycin-polymyxin-bacitracin. Microbiome taxonomy and downstream bacterial richness and evenness were analyzed using microbiome bioinformatics platforms. Results: Accordingly, bacterial taxonomy at the level of phyla and genus was mapped, and alter of antibiotic resistance genes werereported. An increase in the Staphylococcus genus traced during the time and one month following antibiotic treatment. Bacterial network, alpha, and beta diversity indicated a significant microbiota change at the genus level. Conclusion: This study highlights the effect of commonly used ocular antibiotics on commensal microbiota and the emergence of the antibiotic-resistant genus.